Synergistic induction of CX3CL1 by TNF alpha and IFN gamma in osteoblasts from rheumatoid arthritis: involvement of NF-kappa B and STAT-1 signaling pathways - Kuninobu Wakabayashi; Tsuyoshi Odai; Ryo Takahashi; Tsuyoshi Kasama; Takeo Isozaki; et al (Dove Medical Press, 2008)
Takeo Isozaki, Tsuyoshi Kasama, Ryo Takahashi, Tsuyoshi Odai, Kuninobu Wakabayashi, Hirohito Kanemitsu, Kyoko Nohtomi, Hiroko T Takeuchi, Satoshi Matsukura, Masakazu TezukaDivision of Rheumatology, Department of Internal Medicine, Showa University School of Medicine, Tokyo, Japan, and the Department of Orthopedics, Denencyofu Central Hospital, Tokyo, JapanAbstract: To explore the regulation of CX3CL1 in inflammatory bone diseases, CX3CL1 expression by osteoblasts (OB) was examined. Human OB isolated from rheumatoid arthritis (RA) patients, osteoarthritis patients, and normal individuals were incubated in the presence of cytokines. Soluble CX3CL1 levels were determined with an enzyme-linked immunosorbent assay. Expression of CX3CL1 mRNA was examined using quantitative real-time polymerase chain reaction. Although tumor necrosis factor (TNF)-α or interferon (IFN)-γ alone RA OB induced negligible CX3CL1 secretion, the combination of TNF-α and IFN-γ induced dramatic increases in both soluble CX3CL1 protein and mRNA transcripts. This synergistic effect was more pronounced in OB from RA than in OB from either osteoarthritis or normal individuals. The expression of CX3CL1 was markedly reduced by specific inhibitors of the nuclear factor-κB (NF-κB) or STAT-1 transcription factor. These findings suggest that osteoblasts are an important cellular source of CX3CL1 and may play roles in inflammatory bone/joint diseases.Keywords: osteoblast, CX3CL1, chemokine, NF-κB, STAT-1